Feminized Migration in East and Southeast Asia: Policies, Actions and Empowerment - Nicola Piper; Keiko Yamanaka (United Nations Research Institute for Social Development (UNRISD), 2005)
Since the 1980s, labour migration has been increasingly feminized in East and Southeast (hereafter E/SE) Asia. By the beginning of the twenty-first century, more than two million women were estimated to be working in the region, accounting for one third of its migrant population. Most female migrants are in reproductive occupations such as domestic work and sex services, in private households and informal commercial sectors. Despite the great need to protect their welfare and human rights, governments of their destination countries view migrants as merely a workforce to meet labour shortages, and ignore protective measures and gender-sensitive policies. Under pressure to increase foreign revenues, labour-source countries encourage their women to migrate and remit their earnings from aborad, but in the face of global competition, governments of source countries have shown little interest in their migrant women's welfare. In the context of the E/SE Asian countries' bleak records of human rights practices, non-state actors have assumed increasing importance in advocating migrants' rights, which they have done through local and transnational networks. Feminized, and therefore gendered, migration in E/SE Asia has its roots in the region's rapid but uneven economic development, which is characterized by the inequality and conflict that differences of gender, class and nationality produce. The transfer of foreign women within the region from the low-income economies (the Philippines, Indonesia, Viet Nam, Pakistan, Bangladesh among others) to the high-income ones (Singapore, Malaysia, Hong Kong Special Administrative Region (SAR), China (Taiwan Province), the Republic of Korea and Japan) intensifies existing gender inequality, economic injustice and ethnic discrimination. International migration is, however, a contradictory process that, while providing migrant women with opportunities for social mobility, also subjects them to abuses and exploitation. The majority of Asia's migrant women are independent contract workers seeking employment abroad in order to augment family incomes and personal savings. Empowerment results from their everyday resistance to existing power structures, and from the opportunity to accumulate individual and collective resources. An analysis of Asia's immigration policies and women's migration patterns reveals six widely recognized and designated categories and characteristics of the women involved: domestic workers · entertainers (sex workers) · unauthorized workers · immigrant wives · Skilled workers · workers who share an ethnic heritage with that of the host population (such as Japanes-Brazilians in Japan and Korean-Chinese in the Republic of Korea)...
Keywords: 330